Determinants of 25-hydroxyvitamin D Status in a Cutaneous Melanoma Population - Julie De Smedt; Sofie Van Kelst; Laudine Janssen; Vivien Marasigan; Veerle Boecxstaens; Marguerite Stas; Dirk Vanderschueren; Ipek Guler; Kris Bogaerts; Katleen Vandenberghe; Oliver Bechter; Jaak Billen; et al. (Medical Journals Sweden, 2022)
Vitamin D status is influenced by well-known determinants, but factors associated with low 25-hydroxyvitamin D levels in the cutaneous melanoma population are not well defined. The aim of this study was to confirm the well-known determinants and to assess new determinants for 25-hydroxyvitamin D levels in a cutaneous melanoma population. In a prospectively included cohort of 387 patients with cutaneous melanoma the association of 25-hydroxyvitamin D levels with sex, age, body mass index, time of blood withdrawal, Fitzpatrick phototype, vitamin D supplementation, score for intensity of lifetime sun exposure, smoking, education level, hair and skin colour, eye colour, total number of benign naevi, freckles and parameters of chronic sun damage was investigated. In addition, 25-hydroxyvitamin D levels were correlated with pathological parameters of the primary tumour and melanoma stage (8th edition of the American Joint Committee on Cancer (AJCC). Univariate and multivariate logistic regressions were performed using R software. The following factors had a significant effect on vitamin D status: body mass index, seasonal time of blood sampling, vitamin D supplementation, and a subtype of skin, and hair colour.